Dropout prevention in Secondary VET from different learning spaces: A social discussion experience - Francesca Salvà; Carme Pinya; Nuria Álvarez; Aina Calvo (International Journal for Research in Vocational Education and Training (IJRVET), 2019)
Context: In 2016, the early leaving from education and training (ELET) rate in the Balearic Islands, Spain, was 26.8%. According to the most recent data, the participation rate in intermediate vocational education and training (VET) was 31.5%, and the graduation rate was 53.2%. In this paper, we present the main elements of the social agreement among political and social actors, derived from social discussion, which may form the main building blocks for addressing the problems of ELET and, more specifically, dropout in VET. Approach: The social discussion was developed under the need for a broader and more inclusive vision between the formal education system and the community as well as among their agents and initiatives, the mutual understanding between the educational strategies and the models of formal and non-formal education systems and the need for a dynamic and holistic approach to experiential learning processes. As researchers, we analysed the video-recorded content of participants' contributions using three categories: problems, strategies for improvements and contributions of the work group to the social agreement. Findings: The experience evidenced the severity of the ELET problem in the Balearic Islands and proved that preventing ELET and returning people between the ages of 16 and 24 to education and training programmes must become political priorities. The social agreement reflects the consensus reached regarding the need to work in networks, encourage collaboration between formal and non-formal education and emphasise the central role of the community and the active participation of students. The proposed actions regarding VET focus on the need to establish a system that integrates VET from education and from employment systems and the need to increase the offer to connect with the needs of businesses, the territory and a new model of production. The necessity of improving the quality of the system, moving towards more inclusive education and training teachers to recognize and reduce dropout risk factors was also brought up. Conclusion: The social agreement is possible even in contexts with little tradition. The innovation of this experience lies in its equating all participants at the same level of discussion. We highlight the intersection of the variety of positions that emerged in the debates as well as the consensus reached regarding the suggested proposals to address the problem of ELET and dropout in VET in the Balearic Islands.
Keywords: 330; Early leaving from education and training (ELET); Dropout; Vocational Education and Training; Community and Experiential Learning; VET